ASSESSMENT OF STAND GROWTH AND SLENDERNESS COEFFICIENT OF NAUCLEA DIDERRICHII A. CHEV AND TERMINALIA IVORENSIS DE WILD AND THUR IN FORESTRY RESEARCH INSTITUTE OF NIGERIA, (FRIN) ARBORETUM, OYO STATE, NIGERIA - Olajiire-Ajayi, Bolanle L.; Ogundana, Oluwasola Abiodun; Adenuga, Dennis Akinjide (FUDMA JOURNAL OF SCIENCES, 2024)
The contribution of trees to human well-being cannot be overemphasized. The study assessed the growth characteristics and Slenderness Coefficient (SLC) of Nauclea diderrichii and Terminalia ivorensis two tree species in Forestry Research Institute of Nigeria (FRIN) Arboretum. A complete sampling of all trees encountered in each plantation were counted and their Diameter at breast height (Dbh) and total height (Ht) were measured using Haga altimeter and girthing tape respectively. Basal area (BA) and Volume (Vol) were computed using allometric formulae. The mean Dbh, Ht, BA and Vol of Nauclea diderrichii (5.870.27; 7.65± 0.87; 0.004±0.00; 0.016 ±0.0011); Terminalia ivorensis (26.18±1.00; 12.4±0.338; 0.06 ±0.004; 0.38 ±0.029), implying that Terminalia ivorensis had more substantial growth and larger size. More trees (97.43%) of the total trees encountered in both plantation were in the low SLC > 70 category while the remaining were in the medium to high SLC Class. The correlation matrix shows negative correlation between DBH, BA, Vol and SLC which implies more stable trees in the arboretum. The study recommends selecting logging of the trees in the high SLC class as they are vulnerable to wind throw.